Visual memory uniquely predicts anhedonia in schizophrenia but not bipolar disorder. Issue 1 (17th April 2017) - Bodapati, Anjuli S.; Jenkins, Lisanne M.; Sharma, Rajiv P.; Rosen, Cherise
Abstract : Objective: Deficits in memory have been suggested as an influential mechanism of anhedonia, because while pleasant experiences may be enjoyed in‐the‐moment, the cognitive processes involved in reporting anticipated or remembered enjoyable experiences is thought to be impaired. This study will determine whether any aspects of memory, including visual memory, verbal memory or working memory, are significantly predictive of anhedonia in a sample of schizophrenia, psychotic bipolar disorder and healthy controls. Methods: The study included 38 individuals with schizophrenia, 19 individuals with bipolar disorder with psychosis, and 43 age‐matched healthy controls. All participants completed a self‐report social and physical anhedonia questionnaire along with a cognitive screening battery, which assessed the domains of attention/vigilance, working memory, verbal learning, visual learning, and reasoning and problem‐solving. Results: Anhedonia scores were regressed onto domain scores to determine which areas of cognition uniquely predicted level of anhedonia in each group. For the schizophrenia group, physical anhedonia was significantly predicted by worse visual memory performance. The regression models did not find significant cognitive predictors of physical or social anhedonia in the bipolar disorder or control groups. Conclusions: This study found a significant relationship between visual memory and physical anhedonia in schizophrenia patients that was not present in a sample of psychotic bipolar patients or healthy controls, adding to an accumulating body of evidence that visual memory is related to anhedonia in schizophrenia. This relationship may be explained by underlying abnormalities in the orbitofrontal cortex in schizophrenia.